Der junge Horkheimer: Ein Essay zum 50. Todestag des Begründers der Frankfurter Schule - Münster, Arno (Verlag Karl Alber, 2023)
Max Horkheimer, the founder of the critical theory of the ‘Frankfurt School’, died in July 1973. In his essay dedicated to this great thinker, sociologist and philosopher, the author attempts to uncover the theoretical roots of this critical thinking in the philosopher's early work. He analyses Horkheimer's early commitment to the cause of the victims of social, economic and political oppression as well as all systems that trample on the freedom and dignity of the individual and that discriminate against and persecute minorities. He also pays special attention to Horkheimer's struggle against the authoritarian state, against totalitarianism as well as anti-Semitism.